Management Control Mechanisms and Organizational Performance Alignme (gjstudies, 2024)
This research introduces a novel, multi-dimensional framework for conceptualizing the alignmentbetween management control mechanisms (MCMs) and organizational performance, moving beyond traditional linear and contingency models. We argue that prevailing literature, which oftentreats MCMs as discrete tools to be applied for predictable outcomes, fails to capture the complex,emergent, and co-evolutionary nature of control-performance dynamics. Our study posits that alignment is not a static state to be achieved but a continuous process of dynamic fit, characterized byreciprocal influence and adaptive learning between control systems and performance trajectories.We develop and apply a ’Cybernetic-Interpretive’ methodology, an original hybrid approach thatintegrates principles from organizational cybernetics with interpretive phenomenological analysis.This allows for the simultaneous examination of the structural, procedural aspects of control (the’hard’ cybernetic loop) and the lived, subjective experiences of organizational actors enacting andbeing shaped by these controls (the ’soft’ interpretive loop). Through a longitudinal, multi-casestudy of three organizations undergoing strategic transformation, we collected rich qualitative datavia iterative interviews, participatory observation, and archival analysis over an 18-month period.Our findings reveal a previously under-theorized phenomenon: ’Performative Resonance.’ This occurs when the symbolic and ritualistic aspects of MCMs (e.g., the narrative around a new budgetingsystem) generate shared meaning and emotional energy among employees, which in turn amplifiesthe technical efficacy of the controls and directly influences performance outcomes in non-linearways. We demonstrate that high alignment is less about selecting the ’right’ control mix and moreabout fostering an organizational milieu where controls and performance metrics are in a state ofconstructive dialogue, capable of mutual adaptation. The paper concludes by outlining the implications of this dynamic alignment model for theory, challenging the instrumentality of control, and forpractice, suggesting managers should focus on cultivating ’alignment capacities’ rather than implementing optimal designs.